Cardiovascular health metrics and risk of heart failure in a Finnish population: a prospective cohort study. (25th January 2023) - Isiozor, Nzechukwu M.; Kunutsor, Setor K.; Voutilainen, Ari; Isiozor, Ifeanyichukwu; Gaye, Bamba; Kauhanen, Jussi; Laukkanen, Jari A.
Abstract: Aims: This study aimed to examine the association between cardiovascular health (CVH) metrics and the risk of heart failure (HF) in a Finnish population. Methods and results: We used the prospective population‐based Kuopio Ischaemic Heart Disease cohort study comprising men aged 42–60 years at baseline (1984–89) and women aged 53–73 years at baseline (1998–2001). The CVH scores were computed from American Heart Association's CVH metrics for 2385 men and 825 women without a history of HF at baseline. The CVH scores, ranging from 0 to 14, were categorized into three: inadequate, average, and optimal groups. Multivariable Cox regression models were used to estimate the hazard ratios (HRs) and 95% confidence intervals (CIs) for HF. During a median follow‐up period of 27 years for men, and 18 years for women, 465 and 124 HF events were recorded, respectively. The mean ages for men and women were 53 and 63 years, respectively. One hundred and thirty‐three men (5.6%) and 73 women (8.8%) had five or more ideal CVH metrics. Participants with optimal CVH scores had a 64% and 48% lower risk of HF when compared with those with inadequate CVH scores among men and women, respectively (HR, 95% CI: men = 0.36, 0.26–0.49, P < 0.01; women = 0.52, 0.31–0.89, P = 0.02). Conclusions: Optimal CVH metrics is associated with a lower risk of HF among an ageing Finnish population. Optimal CVH score should be targeted among the general population to reduce the risk of HF.